History of Arbovirus Research in the Czech Republic - Hubálek, Zdenek (Viruses, 2021)
The aim of this review is to follow the history of studies on endemiv arboviruses and the diseases they cause which were detected in the Czech lands (Bohemia, Moravia and Silesia (i.e., the Czech Republic)). The viruses involve tick-borne encephalitis, West Nile and Usutu flaviviruses; the Sindbis alphavirus; Ťahyňa, Batai, Lednice and Sedlec bunyaviruses; the Uukuniemi phlebovirus; and the Tribeč orbivirus. Arboviruses temporarily imported from abroad to the Czech Republic have been omitted. This brief historical review includes a bibliography of all relevant papers.
Keywords: Animals; Arbovirus Infections; History, 20th Century; mosquitoes; ticks; arthropods; lidé; dějiny 20. století; arbovirové infekce; arboviry; Czech Republic; birds; History, 21st Century; mammals; Česká republika; Arboviruses; zvířata; dějiny 21. století; Humans